Melle. Sontag: Lithographie d'après nature par Vigneron - Vigneron, Pierre Roch, 1789-1872 (artist):::Creator::::::::::::; Villain, Jean-François, 1818-1852 (printer):::Contributor:::::::::::: (France; England; Paris; London; chez Gihaut frères; chez Engelmann Graf Coindet & Cie.)
Lithographed portrait of Henriette Sontag.